Cadmium stress induces gut microbiota imbalance and consequent activation of the gut–liver axis leading to liver injury and inflammation response in largemouth bass (Micropterus salmoides) - Jiang, Li; Wu, Qiuhong; Bao, Songsong; Fan, Guang; Yang, Zhiwen; Zhou, Pan; Yang, Xiaofei; Liu, Xinyue; Zhou, Xinhong; Wang, Yachao (Frontiers in Marine Science, 2024)
In recent years, cadmium pollution has increasingly serious impacts on aquatic environments, directly threatening the health and growth of freshwater fish and causing significant economic losses to the aquaculture industry. However, there is limited research on the effects of cadmium on the gut-liver axis and hepatotoxicity in freshwater fish. Therefore, this study investigated the potential toxic effects of cadmium induction through the gut-liver axis on largemouth bass. This experiment was divided into four groups, each with different concentrations of cadmium solution added to the water (0.00 mg/L, 1.024 mg/L, 1.537 mg/L, 2.306 mg/L), with three replicates per group, and a feeding period of 42 days. The research findings indicate a significant decline in the growth performance of largemouth bass under cadmium stress (P<0.05). Cadmium-induced oxidative stress inhibited the activity of antioxidant enzymes, activated the Nrf2-Keap1 antioxidant pathway, resulting in increased levels of MDA and ROS, and decreased activities of CAT, GSH-PX, and SOD antioxidant enzymes, as well as related gene expressions (P<0.05). Additionally, cadmium down-regulated the expression of IL-10 and up-regulated the expression of IL-15, IL-8, IL-1β, TNF-α, and MT, indicating an inflammatory response in the liver (P<0.05). Tissue section observations after cadmium stress revealed hepatocyte nuclear condensation, cell degeneration, necrosis, and vacuolization, as well as shortened intestinal villi and intestinal epithelial cell metaplasia. Furthermore, cadmium down-regulated the expression of intestinal barrier-related proteins ZO-1 and Occludin (P<0.05), reducing intestinal microbial diversity. Correlation analysis revealed a close relationship between intestinal microbiota and hepatic immune factors. In summary, cadmium stress can disrupt the intestinal barrier, alter the structure of intestinal microbiota, and the gut-liver axis may potentially play a role in the toxicity of intestinal microbiota and liver.